2021
DOI: 10.3168/jds.2020-18881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corn grain endosperm type and conservation method on feed intake, feeding behavior, and productive performance of lactating dairy cows

Abstract: Our objective was to evaluate the effects of corn grain varying in endosperm type and conserved as high-moisture or dry ground corn on dry matter intake (DMI), feeding behavior, ruminal fermentation, and yields of milk and milk components of cows in early to midlactation. Seven ruminally and duodenally cannulated Holstein cows (73 ± 39 d in milk; mean ± SD) were used in a duplicated 4 × 4 Latin square design with 21-d periods. A 2 × 2 factorial arrangement of treatments was used with main effects of corn grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…[42]. This study indicated that feeding HMEC resulted in increased concentrations of ruminal acetic acid as well as TVFA, consistent with the discoveries reported by Allen et al [43]. Production of acetic acid is intricately linked to the degradation of fiber [38].…”
Section: Discussionsupporting
confidence: 91%
“…[42]. This study indicated that feeding HMEC resulted in increased concentrations of ruminal acetic acid as well as TVFA, consistent with the discoveries reported by Allen et al [43]. Production of acetic acid is intricately linked to the degradation of fiber [38].…”
Section: Discussionsupporting
confidence: 91%
“…A large dataset from commercial Canadian dairy farms revealed that dry and high-moisture maize resulted in similar milk output of dairy cows [10], as well as a meta-analysis of published experiments [11]. Allen and Ying [12] found a slightly lower milk protein content of the high-moisture maize compared to dry maize, while, otherwise, the production results were equal. Torres et al [13] conducted a meta-analysis comparing dry and moist cereal grains based on 18 studies (17 using maize and 1 using barley grain).…”
Section: Feed Intake and Production Responsesmentioning
confidence: 99%
“…As a preservation method, ensiling of grains is cost-and energy-effective compared to drying [8]. Generally similar milk production responses have been achieved with dry and moist cereals whether being based on maize [10][11][12][13] or barley [14,15], although Pettersson et al [16] reported a slight decrease in milk production when moist barley compared with dry barley was fed. Moist maize has increased total-tract starch digestibility and affected rumen fermentation pattern when compared with dried maize [11,12], but less information is available on the effects of barley preservation method on these parameters.…”
Section: Introductionmentioning
confidence: 99%